1985
DOI: 10.1128/jcm.22.2.270-273.1985
|View full text |Cite
|
Sign up to set email alerts
|

Practical recommendations for the detection of pediatric respiratory syncytial virus infections

Abstract: In our private clinic-hospital setting, respiratory syncytial virus (RSV) was isolated from infants more frequently and sooner from nasal washes (84%; 4.2 days) than from throat swabs (45%; 5.5 days) or nasopharyngeal swabs (39%; 5.7 days). Immunofluorescence of nasal wash cells identified 72% of the infants with virus isolations from nasal washes in less than one day. We therefore recommend the combination of isolation and immunofluorescence on nasal wash specimens for optimal detection of RSV-infected infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 8 publications
(5 reference statements)
1
16
0
Order By: Relevance
“…However, the availability of specific therapy for RSV infections and the necessity of monitoring these infections with regard to epidemiological measures underlines the importance of rapid and efficient diagnostic methods. Direct or indirect immunofluorescent staining preferably with monoclonal antibodies has been successfully used until now in the diagnosis of RSV (2,11,12). With regard to rapidity, DFA tests have the potential advantage of eliminating the unnecessary use of antibiotics and shortening the hospitalization period, by cutting down the time spent reaching the right diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the availability of specific therapy for RSV infections and the necessity of monitoring these infections with regard to epidemiological measures underlines the importance of rapid and efficient diagnostic methods. Direct or indirect immunofluorescent staining preferably with monoclonal antibodies has been successfully used until now in the diagnosis of RSV (2,11,12). With regard to rapidity, DFA tests have the potential advantage of eliminating the unnecessary use of antibiotics and shortening the hospitalization period, by cutting down the time spent reaching the right diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DFA tests are stated to be more sensitive than cell culture (2,8). The factors that contribute to the inefficiency of cell culture are as follows: the significant loss of infectivity of RSV in stored specimens, the lability of the virus, the sensitivity of the host cell line to the virus, the duration of the disease at the time material is collected, the presence of RSV-specific secretory antibodies which can neutralize the virus in specimens, and the type of material used for inoculation (8,11,12). Furthermore, DFA staining provides the opportunity to make a diagnosis even if the culture is contaminated, such as was the case in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies in developed countries have indicated that the source of specimens influences the likelihood of RSV detection (Hall & Douglas 1975; McIntosh et al . 1982; Treuhaft et al . 1985; Ahluwalia et al .…”
Section: Introductionmentioning
confidence: 99%
“…Nasal swabs, throat swabs, tracheal aspirates, nasal washes, and nasopharyngeal aspirates have all been tested for their efficiency of recovery of virus in cell culture. Nasal washes have been shown to be superior to swabs or aspirates of tracheal secretions (84). Direct aspiration of secretions into polyethylene catheters is also an effective method of obtaining secretions (23).…”
Section: Diagnostic Methodsmentioning
confidence: 99%